Pseudoaneurysm of the left gluteal artery after a pelvic fracture sustained during the Marmara earthquake: Report of a case - YEGEN, ŞEVKET CUMHUR (SPRINGER-VERLAG, 2001)
Although iliac artery injuries caused by pelvic fractures are uncommon, in special circumstances, such as earthquakes, traumatic arterial injury should be carefully investigated. This reports describes a case of an iliac artery pseudoaneurysm causing compressive symptoms that was successfully treated by radiologic embolization.
Keywords: pseudoaneurysm; pelvic trauma; angiography; embolization; iliac artery; VASCULAR INJURIES; FALSE ANEURYSM